Process evaluation and exploration of telehealth in motor neuron disease in a UK specialist centre - Susan Mawson; Cindy Cooper; Mike Bradburn; Pamela J Shaw; Ann Quinn; Theresa Walsh; Esther Hobson; Wendy Baird (BMJ Open)
Objectives To evaluate the processes involved in using a novel digitally enabled healthcare system (telehealth in motor neuron disease (TiM)) in people living with motor neuron disease (MND) and their informal carers. We examined TiM implementation, potential mechanisms of impact and contextual factors that might influence TiM implementation or impact.Design An 18-month, single-centre process evaluation within a randomised, pilot and feasibility study.Intervention TiM plus usual care versus usual care alone.Setting A specialist UK MND care centre.Participants 40 patients with MND and 37 primary informal carers.Primary and secondary outcome measures Patient, carer and staff outcomes and experiences using semistructured interviews. Descriptive data on implementation and use of TiM.Results The TiM was acceptable and accessible to patients, carers and staff. Intervention uptake and adherence were good: 14 (70%) patients completed a TiM session at least fortnightly. Barriers to TiM use (such as technology experience and disability) were overcome with well-designed technology and face-to-face training. Reported potential benefits of TiM included improved communication and care coordination, reassurance, identification of complications and the potential for TiM to be an alternative or addition to clinic. Benefits depended on patients’ current level of needs or disability. The main challenges were the large number of alerts that were generated by TiM, how the clinicians responded to these alerts and the mismatch between patient/carer expectations and nurses actions. This could be improved by better communication systems and adjusting the alerts algorithm.Conclusion TiM has the potential to facilitate access to specialist care, but further iterative developments to the intervention and process evaluations of the TiM in different services are required.Trial identifier number ISRCTN26675465.